2018
DOI: 10.1007/s12524-018-0917-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Urban Impervious Surface from WorldView-2 and Airborne LiDAR Data Using 3D Convolutional Neural Networks

Abstract: The urban impervious surface has been recognized as a key quantifiable indicator in assessing urbanization and its environmental impacts. Adopting deep learning technologies, this study proposes an approach of three-dimensional convolutional neural networks (3D CNNs) to extract impervious surfaces from the WorldView-2 and airborne LiDAR datasets. The influences of different 3D CNN parameters on impervious surface extraction are evaluated. In an effort to reduce the limitations from single sensor data, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The deep learning scholars propose next results: overall kappa = 0.89 (Sun et al, 2018a), F 1 of roofs = 0.93 and F 1 of impervious surfaces = 0.90 (Yang et al, 2017), F 1 score of buildings = 0.95 (Sun et al, 2018b); that is close to the mean F 1 score for ISPRS data (WEB, b). Therefore, it can be concluded, that the proposed method has potential, which is comparable to deep learning methods, but it does not require training and the high-performance computing as deep learning solutions.…”
Section: Table 6 Classification Rules Of Buildingssupporting
confidence: 64%
See 1 more Smart Citation
“…The deep learning scholars propose next results: overall kappa = 0.89 (Sun et al, 2018a), F 1 of roofs = 0.93 and F 1 of impervious surfaces = 0.90 (Yang et al, 2017), F 1 score of buildings = 0.95 (Sun et al, 2018b); that is close to the mean F 1 score for ISPRS data (WEB, b). Therefore, it can be concluded, that the proposed method has potential, which is comparable to deep learning methods, but it does not require training and the high-performance computing as deep learning solutions.…”
Section: Table 6 Classification Rules Of Buildingssupporting
confidence: 64%
“…And the understandable supervised solution, expected high precision, available open data, plenty of training courses and simple tuning model only increases the number of deep learning scholars. Therefore, nowadays, the deep learning is massively used for image classification including LiDAR data processing (Yang et al, 2017;Rizaldy et al, 2018;Sun et al, 2018aSun et al, , 2018b. The deep learning is based on the application of the artificial neural networks and it is intuitive to use 2D projection of LiDAR data as input that is actually applied in practise.…”
Section: Table 6 Classification Rules Of Buildingsmentioning
confidence: 99%
“…In their review, Ma et al [26] showed that nearly 200 publications using deep convolutional neural networks (CNNs) have been published in the field of remote sensing by early 2019 of which most focused on land use land cover (LULC) classification [28], urban feature extraction [29][30][31], and crop detection [32,33]. Deep learning approaches often require a large amount of training data, and there are benchmark datasets publicly available for training and testing of deep learning approaches in the abovementioned remote sensing fields.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the popular solution for semantic segmentation is deep learning. For example, deep learning scholars propose next results for building detection using airborne LiDAR data: overall kappa -0.89 [8] and F1 score 0.93 [9] and 0.95 [10]. So, the accuracy of graph-cut method, which provided kappa 0.888 and F1 score 0.933 (recalculating confusion matrix), is comparable with deep learning solutions.…”
Section: (R) the Number Of Classified Buildings In Tables Ii-v Is Different Comparing With Table I Because Tablementioning
confidence: 99%